ANALISIS PERLAKUAN AKUNTANSI ASET TETAP PADA PT. MUARA DUA PALEMBANG BERDASARKAN SAK ETAP NO. 15 - Rizal Effendi; Kartawinata Kartawinata (Jurnal RATRI (Riset Akuntansi Tridinanti), 2021)
In the face of fierce competition in the business world, companies must strive to maintain increased profits or profits within the company. The increase that occurred in the company can be seen from its financial statements, because these reports are used to evaluate the condition of the company and to estimate the results of operations and cash flows in the future.Financial reports are a medium of communication and information for internal and external parties of the company. One form of financial statements is the income statement and balance sheet. The income statement reports income and expenses over a certain period of time whereas the balance sheet reports the total assets, liabilities and owner's equity as of a specific date. Financial statements must be presented appropriately and accurately because the financial statements will be used as one of the considerations for decision making in the future.